PENGARUH KINERJA KEUANGAN MEMPREDIKSI PERTUMBUHAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERBANKAN - Rini Handayani; Aurora Angela (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2023)
The purpose of this study is to examine the role of financial performance in forecasting profit growth for companies operating in the banking industry listed on the Indonesia Stock Exchange for the period 2018-2020. All companies listed on the IDX served as the study population, and companies active in the banking industry listed on the IDX between 2018 and 2020 served as research samples. In this work, multiple linear regression and moderation regression analysis were used as test methodologies. Based on the results of tests conducted using SPSS, it was found that Company Size can strengthen the effect of Net Profit Margin, Capital Adequacy Ratio and Interest Risk Ratio on Profit Growth but Company Size cannot moderate the effect of Non-Performing Loans on Profit Growth. Keywords: NPM, CAR, NPL, IRR, Company Size, Profit Growth